Implementasi Pembelajaran Berbasis Proyek untuk Meningkatkan Kemandirian Siswa Sekolah Dasar - Jeni Pristiawati; Nur Azmi Alwi; Inggria Kharisma (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to investigate the implementation of project-based learning (PjBL) in improving students independence at the elementary school students. Independent learning is a crucial aspect in students' academic and personal development enable them to take their own steps, organize themselves, and take responsibility for their learning process. Through a classroom action study approach, this study involved students and teachers in several elementary school classes implementing PjBL in various subjects. Data were obtained through observation, interview interactions, and examination of project documents made by students. The research findings indicate that the implementation of PjBL significantly improves various aspects of student independence, such as the ability to plan, implement, and assess tasks independently, as well as encouraging student motivation and confidence in learning. Challenges and strategies for effective PjBL implementation were also identified in this study, providing practical insights for educators who wish to apply this approach to empower the independence of elementary school students' learning.